Inventário florístico de floresta natural na área da estrada Cuiabá-Porto Velho (BR - 364) - Absy, Maria Lúcia; Prance, Ghillean Tolmie; Barbosa, Edelcilio Marques (Acta Amazonica, 1987)
Forest inventories were made on terra £firme within the area οf human influence along the Cuiabá-Porto Velho Highway (BR-364)in the state οf Rondônia. One transect measuring 10 x 1000m was located in the municipality oi Jam, branch road 605. Two transects, each measuring 10 x 2000m, were done at Projeto Machadinho, branch roads MC-2and MA-9. The forest is of medium height and has a total 278different species represented by 2.235 individuals and 57 families in the six hectares. Hectares I and II, at Jaru, have a floristic diversity of 113 and 136species of 10cm or more diameter (DBH). Hectares III,IV, V and VI at Projeto Machadinho have, respectively, 103,115, 122and 121tree species of 10cm or more DBH.The most important species found in hectare I is breu manga (Tetragastris altissima(Aubl.) Swartz), with an IV of 12.07 (4,0% of total IV); in hectare II, muiraquatiara(Astronium lecointeiDucke),with and IV of 28.94 (9,6%of total IV); in hectare III, Macrolobiumsp., with an IV of 28.94 (9,6%of total IV); in hectare IV, pan d'alho (Gallesia integrifolia(Spreng.) Harms), ωith and IV of 39.41 (13,1%of total IV); in hectare V, tauari (Couratari macrosperma.A. C. Smith), with an IV of 11.32 (3,8%of total IV); in hectare VI, violeta (Peltogyne catingae Ducke subsp. glabra (W. Rock. ) M. F. da Silva), with an IV of 11.68 (3,9%of total IV).The six most important families in order of importance are Leguminosae, Moraceae, Sapotaceae, Lecythidaceae, Burseraceae and Palmae.The quantitative data on natural regeneration show that those species with the greatest number, oi regenerating individuals were: Duguetia flagellaresHuber and Maquirasp. in the Municipio oi Jaru and Coussareasp. and Micrandra.sp in the area of Projeto Machadinho, em Ariquemes.", 'en